Rucaparib versus chemotherapy for treatment of relapsed ovarian cancer with deleterious BRCA1 or BRCA2 mutation (ARIEL4): final results of an international, open-label, randomised, phase 3 trial - Oza, Amit M; Lisyanskaya, Alla; Fedenko, Alexander; de Melo, Andreia Cristina; Shparyk, Yaroslav; Rakhmatullina, Irina; Bondarenko, Igor; Colombo, Nicoletta; Svintsitskiy, Valentyn; Biela, Luciano; Nechaeva, Marina; Lorusso, Domenica; et al. (The Lancet. Oncology, 2025)
BACKGROUND: In the ARIEL4 trial of rucaparib versus standard-of-care chemotherapy in patients with relapsed BRCA-mutated ovarian carcinoma, the primary endpoint was met, showing improved investigator-assessed progression-free survival with rucaparib. Here, we present the final overall survival analysis of the trial and other post-progression outcomes. METHODS: This open-label, randomised, controlled phase 3 trial was done at 64 hospitals and cancer centres in 12 countries, including Brazil, Canada, Czech Republic, Hungary, Israel, Italy, Poland, Russia, Spain, Ukraine, the UK, and the USA. Eligible patients were women aged 18 or older with BRCA1 or BRCA2-mutated ovarian carcinoma and had received at least two previous chemotherapy regimens. Patients had to have evaluable disease as per Response Evaluation Criteria in Solid Tumors (RECIST; version 1.1) criteria and an Eastern Cooperative Oncology Group performance status of 0 or 1. Patients were randomly assigned (2:1) using an interactive response technology and block randomisation (block size of six) and stratified by progression-free interval after the most recent platinum-containing therapy to receive oral rucaparib (600 mg twice daily administered in 28-day cycles) or chemotherapy on the basis of platinum-sensitivity status. In the chemotherapy group, patients with platinum-resistant disease (progression-free interval ≥1 to <6 months) or partially platinum-sensitive disease (progression-free interval ≥6 to <12 months) received weekly paclitaxel (starting dose 60-80 mg/m2 on days 1, 8, and 15). Patients with fully platinum-sensitive disease (progression-free interval ≥12 months) received the investigator's choice of platinum-based chemotherapy (single-agent cisplatin or carboplatin, or platinum-doublet chemotherapy), in 21-day or 28-day cycles. The primary endpoint (previously reported) was investigator-assessed progression-free survival, assessed in the efficacy population (all randomly assigned patients with deleterious BRCA1 or BRCA2 mutations without reversion mutations) and in the intention-to-treat population (all randomly assigned patients). Overall survival was a prespecified secondary endpoint and was analysed in the intention-to-treat population. Safety was assessed in all patients who received at least one dose of assigned study treatment. The cutoff date was April 10, 2022. This study is registered with ClinicalTrials.gov, NCT02855944; enrolment is complete and the study is closed. FINDINGS: Between March 1, 2017, and Sept 24, 2020, 349 eligible patients were randomly assigned to receive rucaparib (n=233) or chemotherapy (n=116). 332 (95%) of 349 patients were white and 17 (5%) patients were other or of unknown race. In the chemotherapy group, 80 (69%) of 116 patients crossed over to receive rucaparib. Median follow-up was 41·2 months (IQR 37·8-44·6). At data cutoff for this final analysis (April 10, 2022), 244 (70%) of 349 patients had died: 167 (72%) of 233 in the rucaparib group and 77 (66%) of 116 in the rucaparib group. Median overall survival was 19·4 months (95% CI 15·2-23·6) in the rucaparib group versus 25·4 months (21·4-27·6) in the chemotherapy group (hazard ratio 1·3 [95% CI 1·0-1·7], p=0·047). No new safety signals were observed, including during crossover to rucaparib. The most common grade 3-4 adverse events across treatment groups included anaemia or decreased haemoglobin (reported in 59 [25%] of 232 patients in the rucaparib group and seven [6%] of 113 in the chemotherapy group), and neutropenia or decreased neutrophil count (in 26 [11%] of 232 in the rucaparib group and 16 [14%] of 113 patients in the chemotherapy group). Serious adverse events were reported in 66 (28%) of 232 patients in the rucaparib group and 14 (12%) of 113 patients in the chemotherapy group. Ten treatment-related deaths were reported in the rucaparib group, two of which were linked to judged to be related to rucaparib (cardiac disorder and myelodysplastic syndrome), and one death related to treatment was reported in the chemotherapy group, with no specific cause linked to the treatment. INTERPRETATION: These data highlight the need for a better understanding of the most appropriate treatment for patients who have progressed on a poly(adenosine diphosphate-ribose) polymerase (PARP) inhibitor, and the optimal sequencing of chemotherapy and PARP inhibitors in advanced ovarian cancer. FUNDING: Clovis Oncology.
Keywords: indoly; protein BRCA2; Humans; Indoles; lidé středního věku; BRCA1 Protein; Female; mutace; Aged; nádory vaječníků; protokoly protinádorové kombinované chemoterapie; dospělí; Ovarian Neoplasms; senioři; lidé; PARP inhibitory; doba přežití bez progrese choroby; Poly(ADP-ribose) Polymerase Inhibitors; Carcinoma, Ovarian Epithelial; Adult; epiteliální ovariální karcinom; ženské pohlaví; Middle Aged; paclitaxel; protein BRCA1; Antineoplastic Combined Chemotherapy Protocols; Progression-Free Survival; BRCA2 Protein; lokální recidiva nádoru; Paclitaxel; Mutation; Neoplasm Recurrence, Local